If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9(x+3)=3(x+3)
We simplify the equation to the form, which is simple to understand
9(x+3)=3(x+3)
Reorder the terms in parentheses
+(+9x+27)=3*(x+3)
Remove unnecessary parentheses
+9x+27=+3+*(+x+3+)
Reorder the terms in parentheses
+9x+27=+(+3x+9)
Remove unnecessary parentheses
+9x+27=+3x+9
We move all terms containing x to the left and all other terms to the right.
+9x-3x=+9-27
We simplify left and right side of the equation.
+6x=-18
We divide both sides of the equation by 6 to get x.
x=-3
| 1-4n=-n-2 | | x+5forx=-18 | | 4a-5b= | | 49Z+4=54 | | 7y^0= | | (6^3/9)+(18+10)^2 | | 14/5(3/10) | | K=13+5k | | -3=-2/3+v/3 | | 33+17=x-20 | | 8+10y+3y-12= | | -3=-2+v | | 441=x^2+20x | | 0=-1+n/10 | | 100x^2-1=99 | | 28=3n-2 | | 9k+8= | | 8C-5=35 | | 100p^2+9=90 | | 4a^2+9=-19 | | 64x^2=64 | | -7x-3=3-6x | | 3x^2/144=-2x/3 | | 3k+7= | | -10n-40=4n-12 | | -2+36k^2=23 | | (4x-6)/(12x+7) | | p/5+1=0 | | x+2=90 | | x*9+2=90 | | 31.61=6g+3.59 | | 4.89-1.2-5.69=-1.89-2.4 |